2020
DOI: 10.1111/gwao.12455
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond the gender binary: Examining workplace perceptions of nonbinary and transgender employees

Abstract: those who identify outside of the man/woman gender binary. Participants (N = 249) were presented with a vignette which included a description of a fictitious co-worker's sex and gender identity, and asked to rate the co-worker's likeability and perceived job performance. Results revealed that the assigned sex and the gender of hypothetical employees interactively impacted interpersonal and workplace perceptions. For individuals assigned male at birth, identifying as a man led to the most positive ratings, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…We note again that we can only comment on the average conference experiences of scientists who are perceived by others as men or women (e.g., Kalejta & Palmenberg, 2017; Klein et al., 2017). Our study does not account for all gender diversity at the LPSC, nor does it account for gender perception as informed by cultural or social contexts (e.g., Bai et al., 2015; Cuddy et al., 2015; Dray et al., 2020; Nisbett et al., 2001), race (Patterson et al., 1996; Scarborough et al., 2021) or other factors.…”
Section: Methodsmentioning
confidence: 96%
“…We note again that we can only comment on the average conference experiences of scientists who are perceived by others as men or women (e.g., Kalejta & Palmenberg, 2017; Klein et al., 2017). Our study does not account for all gender diversity at the LPSC, nor does it account for gender perception as informed by cultural or social contexts (e.g., Bai et al., 2015; Cuddy et al., 2015; Dray et al., 2020; Nisbett et al., 2001), race (Patterson et al., 1996; Scarborough et al., 2021) or other factors.…”
Section: Methodsmentioning
confidence: 96%
“…Brewster et al (2014) found trans workers experiencing hostility due to their gender orientation in their work environment. In an experimental study, Dray et al (2020) and Rice et al (2021) found lower workplace skills and likeability and poorer job performance of a trans worker compared to a regular worker.…”
Section: Workplace Discriminationmentioning
confidence: 95%
“…For female-to-male (FTM) trans people, this can mean receiving more authority, higher pay, and more respect, with white FTM trans people faring better than of color [56]. Some researchers suggest that without a traditional gender to hold onto, nonbinary people in the workplace are looked on even less favorably [57]. All of these examples point to solutions regarding the workplace more broadly, rather than finding a means to an end for someone's identity.…”
Section: Transgender and Nonbinary Peoplementioning
confidence: 99%